Development of Ethical Guidelines for AI-Assisted Educational Counseling Decisions. - Marliana, Thika; Osman, Suhaila Binti; Agustin, Dinni; Mawarni, Endang Siti; Azija, Izzatul; Trigono, Ahdun; Wahyuningrum, Maria Aditia (Yayasan Minang Darussalam, 2025)
The increasing integration of Artificial Intelligence (AI) in educational counseling has introduced new opportunities and ethical challenges in decision-making processes related to student support services. This study aims to develop a set of ethical guidelines tailored to the use of AI-assisted systems in educational counseling, focusing on transparency, fairness, accountability, privacy, and human oversight. Employing a qualitative methodology, the research synthesizes insights from educational technologists, counseling professionals, AI ethicists, and policymakers through in-depth interviews and Delphi-based consensus. The proposed framework addresses ethical dilemmas arising from algorithmic bias, informed consent, data protection, and the balance between human judgment and machine recommendations. Findings suggest that while AI can enhance efficiency and personalization in counseling, it must operate within clearly defined ethical boundaries to safeguard student autonomy, well-being, and equity. The resulting guidelines are intended to serve as a foundational reference for educational institutions, developers, and regulatory bodies in the responsible deployment of AI in student counseling contexts.